Herbal Compounds and Toxins Modulating TRP Channels - Rudi Vennekens; Joris Vriens; Bernd Nilius (2008)
Although the benefits are sometimes obvious, traditional or herbal medicine is regarded with skepticism, because the mechanism through which plant compounds exert their powers are largely elusive. Recent studies have shown however that many of these plant compounds interact with specific ion channels and thereby modulate the sensing mechanism of the human body. Especially members of the Transient Receptor Potential (TRP) channels have drawn large attention lately as the receptors for plant-derived compounds such as capsaicin and menthol. TRP channels constitute a large and diverse family of channel proteins that can serve as versatile sensors that allow individual cells and entire organisms to detect changes in their environment. For this family, a striking number of empirical views have turned into mechanismbased actions of natural compounds. In this review we will give an overview of herbal compounds and toxins, which modulate TRP channels.